Studi Potensi Tanah Longsor Dan Upaya Pengendaliannya Di Wilayah Sub DAS Konto Hulu - Darmawan, Arif Rahmad; Sholichin, Mohammad; Limantara, Lily Montarcih; Andawayanti, Ussy (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
Landslides often occur in the Upper Konto sub watershed. To anticipate the future landslide, the landslide susceptibility map was made that show the landslide potential areas. Eight thematic maps as landslide susceptibility formula parameters used to develop a landslide susceptibility map that includes three daily maximum cumulative rainfall, slope, geology rocks, the presence of faults, regolith soil depth, land use, the presence of road infrastructure, and population density. Determination of susceptibility value is the sum of the multiplying of scores for each parameter with the weight of each parameter. Based on the value of vulnerability, landslide susceptibility maps generated from the overlay analysis of the multiplication results of the score and weight of the eighth parameters with the Geographic Information Systems (GIS)program. The results of this study is the potential for landslides in the Upper Konto sub watershed consists of not susceptible at 1.24%, slightly susceptible at 12.12%, moderatelysusceptible 84.17%, and susceptible at 2.38%, so do very vulnerable while there but very small. Landslide control efforts can be divided into short-term treatment with mechanical methods in accordance with the level of susceptibility and long-term treatment with vegetative methods in accordance with the area function and the level of susceptibility.Keyword: potential landslides, landslide susceptibility formula, control efforts